Impairments of long‐term depression induction and motor coordination precede Aβ accumulation in the cerebellum of APPswe/PS1dE9 double transgenic mice. (19th April 2014) - Kuwabara, Yuki; Ishizeki, Masato; Watamura, Naoto; Toba, Junya; Yoshii, Aya; Inoue, Takafumi; Ohshima, Toshio
Abstract Alzheimer's disease (AD) is a neurodegenerative disorder that represents the most common type of dementia among elderly people. Amyloid beta (Aβ) peptides in extracellular Aβ plaques, produced from the amyloid precursor protein (APP) via sequential processing by β‐ and γ‐secretases, impair hippocampal synaptic plasticity, and cause cognitive dysfunction in AD patients. Here, we report that Aβ peptides also impair another form of synaptic plasticity; cerebellar long‐term depression (LTD). In the cerebellum of commonly used AD mouse model, APPswe/PS1dE9 mice, Aβ plaques were detected from 8 months and profound accumulation of Aβ plaques was observed at 18 months of age. Biochemical analysis revealed relatively high levels of APP protein and Aβ in the cerebellum of APPswe/PS1dE9 mice. At pre‐Aβ accumulation stage, LTD induction, and motor coordination are disturbed. These results indicate that soluble Aβ oligomers disturb LTD induction and cerebellar function in AD mouse model. <boxed-text content-type="graphic" id="jnc12728-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> APPswe/PS1d9E mice, a commonly used Alzheimer's mouse model, have Aβ plaques in the cerebellum after 8 months old. We show that soluble Aβ impairs LTD induction in the cerebellar slice. APPswe/PS1d9E mice demonstrate defects of motor coordination and LTD induction in the cerebellum at the pre‐Aβ accumulation period.